Lower diocesan theological seminaries in Poland in the light of the current legislation - ADAMCZYK, JERZY (Prawo Kanoniczne, 2015)
The Article explores the canonical aspect of the issue of lower diocesan theological seminaries in Poland. The first part presents the objective of lower theological seminaries in Poland in the light of current legislation. The second part indicates the necessity of adequate formation in the lower diocesan theological seminaries in Poland, and the third part deals with the organizational structure of the schools at stake.